Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

Evaluate the limit:

[tex]\[ \lim _{x \rightarrow \infty}\left(\frac{\ln x}{x}\right)^{1 / \ln x} \][/tex]


Sagot :

To find the limit of [tex]\(\left( \frac{\ln x}{x} \right)^{1 / \ln x}\)[/tex] as [tex]\(x \to \infty\)[/tex], we need to carefully analyze the behavior of the expression as [tex]\(x\)[/tex] grows larger.

[tex]\[ \lim _{x \rightarrow \infty}\left(\frac{\ln x}{x}\right)^{1 / \ln x} \][/tex]

First, let's denote the given expression as [tex]\( f(x) \)[/tex]:

[tex]\[ f(x) = \left( \frac{\ln x}{x} \right)^{1 / \ln x} \][/tex]

Taking the natural logarithm of [tex]\( f(x) \)[/tex] will help simplify the analysis. Let:

[tex]\[ L = \ln(f(x)) = \ln \left( \left( \frac{\ln x}{x} \right)^{1 / \ln x} \right) \][/tex]

Using the logarithm power rule [tex]\( \ln(a^b) = b\ln(a) \)[/tex]:

[tex]\[ L = \frac{1}{\ln x} \ln \left( \frac{\ln x}{x} \right) \][/tex]

Next, we can split the logarithm inside:

[tex]\[ L = \frac{1}{\ln x} \left( \ln (\ln x) - \ln x \right) \][/tex]

Separate the terms in the fraction:

[tex]\[ L = \frac{\ln (\ln x)}{\ln x} - \frac{\ln x}{\ln x} \][/tex]

[tex]\[ L = \frac{\ln (\ln x)}{\ln x} - 1 \][/tex]

Now, we are interested in finding the limit of [tex]\( L \)[/tex] as [tex]\( x \to \infty \)[/tex]:

[tex]\[ \lim_{x \to \infty} L = \lim_{x \to \infty} \left( \frac{\ln (\ln x)}{\ln x} - 1 \right) \][/tex]

Consider each term separately. First, observe the fraction [tex]\(\frac{\ln (\ln x)}{\ln x}\)[/tex]:

As [tex]\( x \to \infty \)[/tex], both [tex]\( \ln x \)[/tex] and [tex]\( \ln(\ln x) \)[/tex] increase, but [tex]\( \ln x \)[/tex] increases much faster than [tex]\( \ln(\ln x) \)[/tex]. Hence, we can conclude:

[tex]\[ \lim_{x \to \infty} \frac{\ln (\ln x)}{\ln x} = 0 \][/tex]

Thus, the limit of [tex]\( L \)[/tex] becomes:

[tex]\[ \lim_{x \to \infty} L = 0 - 1 = -1 \][/tex]

We have determined that:

[tex]\[ \ln(f(x)) \to -1 \][/tex]

Finally, to find the limit of [tex]\( f(x) \)[/tex], we exponentiate both sides:

[tex]\[ f(x) \to e^{-1} \][/tex]

Therefore, the limit is:

[tex]\[ \lim_{x \to \infty} \left( \frac{\ln x}{x} \right)^{1 / \ln x} = e^{-1} \][/tex]

Thus, the answer is:

[tex]\[ e^{-1} \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.